Quality Distortions in Monopolistic Competition - Sergei Kichko; Alina Ozhegova; Alexander Tarasov (CESifo GmbH, 2024)
In this paper, we explore how heterogeneous firms decide on vertical and horizontal qualities of their products. We show that if increasing the product qualities appears to be relatively costly, more productive firms choose higher vertical quality but lower horizontal quality. We also document distortions that arise in our framework. Specifically, we find that in the market equilibrium, firms tend to underinvest in horizontal quality but overinvest in vertical quality compared to the first best allocation. Using data from pizzerias in Oslo, Norway, we provide a calibration exercise to estimate welfare losses due to the quality distortions.
Keywords: D43; L13; 330; monopolistic competition; vertical quality; horizontal quality; welfare